Target reflectivity and RCS interactions in integrated maritime surveillance systems based on surface-wave high-frequency radars. - Sevgi, Levent (IEEE Antennas & propagation magazine.)
Abnormal fluctuations have been observed in detected power levels of some of the targets during trials of the integrated maritime surveillance system (IMS) based on the Canadian east coast surface-wave high-frequency radar (HFSWR). The power level of most of the surface and air targets fluctuated within measurement-error limits (a few dB) during consecutive detections. These fluctuations have been observed to be more than 15 dB for a huge oil platform and nearby large tankers. These fluctuations are quite different than those observed in microwave radars, such as pulse-to-pulse or scan-to-scan fluctuations (which are modeled as different Swerling-type targets), and as are mentioned in most of the classical radar handbooks. In order to understand the reason behind these fluctuations, the behavior of the target reflectivity and radar cross section (RCS) of surface and air targets and their mutual RCS interaction were investigated. Powerful numerical techniques were used to model and understand the target reflectivity and RCS interactions, mostly in the resonance regime. Different scenarios were created, and the mutual RCS behavior of nearby large targets (such as oil tankers and/or fixed offshore oil platforms) as they were maneuvering were modeled. It was shown that 10 dB to 20 dB RCS fluctuations should be expected when targets interact, especially in the resonance regime.